Enhancement of the Implementation of the Philippine Coast Guard National Service Training Program – Civic Welfare Training Service - Cua Jr., Edward Ylanan (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the implementation status of the Philippine Coast Guard National Service Training Program – Civic Welfare Training Service (PCG NSTP-CWTS) with the aim of developing relevant enhancement recommendations. Employing a mixed-methods design, the research involved 300 students who have undergone PCG Oriented NSTP–CWTS, who provided quantitative data through survey, and key implementers and stakeholders who offered qualitative insights via survey and interview. While students generally perceived the program's implementation as "Agree" across curriculum content, teaching-learning activities, and assessment, a notable "Strongly Disagree" rating emerged regarding the curriculum's focus on PCG functions over broader civic welfare activities. Qualitative findings elaborated on this, revealing a significant disconnect between PCG and university curricula, pedagogical limitations in teaching strategies (often military-centric), inconsistencies in instructor qualifications and professional development due to budgetary constraints, and a critical need for formalized university-PCG relationships. The study concludes that despite student satisfaction with practical elements, systemic challenges in curriculum breadth, instructor pedagogy, training standardization, and inter-institutional collaboration impede the program's holistic implementation as mandated by the NSTP Act. Recommendations include establishing a joint curriculum review committee, developing standardized student-centered instructional guides, prioritizing regular and diverse instructor professional development, strengthening university-PCG partnerships, and lobbying for a legislative amendment to formalize the PCG's NSTP function.